Black Petrels (Procellaria parkinsoni) patrol the ocean shelf-break: GPS tracking of a vulnerable procellariiform seabird. - Freeman, R; Dennis, T; Landers, T; Thompson, D; Bell, E; Walker, M; Guilford, T (2010)
BACKGROUND: Determining the foraging movements of pelagic seabirds is fundamental for their conservation. However, the vulnerability and elusive lifestyles of these animals have made them notoriously difficult to study. Recent developments in satellite telemetry have enabled tracking of smaller seabirds during foraging excursions. METHODOLOGY/PRINCIPAL FINDINGS: Here, we report the first successful precision tracking of a c. 700 g seabird, the vulnerable Black Petrel, Procellaria parkinsoni, foraging at sea during the breeding season, using miniature GPS-logging technology. Employing a combination of high-resolution fixes and low-power duty-cycles, we present data from nine individual foraging excursions tracked during the chick-rearing period in February 2006. CONCLUSIONS/SIGNIFICANCE: We provide a snapshot of the species' foraging range and behaviour in relation to detailed underlying bathymetry off the coast of New Zealand, finding a significant relationship between foraging movements and regions of the shelf-break. We also highlight the potential of more sophisticated analyses to identify behavioural phenomena from position data alone.